A design of sequential reversible circuits by reversible gates - Andaloussi, Issam; Brahim Sedra, Moulay (International Journal of Engineering and Technology, 2020)
Reversible logic has become increasingly important in the design of low power CMOS circuits, quantum computing and nanotechnology. In this article we work on recent sequential circuits namely RS Flip Flop JK Flop Flip Flop Flop Flip Flop Master Slave Flip Flop using some reversible gates FG (Feyman Gate), FRG (Fredkin Gate), NG (New Gate) , PG (Peres Gate), BJN (New BJN Gate), while modifying them to obtain new circuits keeping their same functionality and increasing their performances.Â Â Â